Characterization of dry spell events in a basin in the North of Tunisia - Mathlouthi M.; Lebdi F. (Drought management: scientific and technological innovations, 2008)
This contribution focuses on the analysis of dry spells for operation of dams based on an approach different from that of using observations carried out with regular time intervals. The case study is localized around the Ghézala dam in Northern Tunisia having a Mediterranean climate. Dry events are composed of series of dry days separated by rainfall events. Rainfall events are defined by uninterrupted series of rainfall days containing at least one day with a precipitation amount superior or equal to a threshold of 4 mm. The rainfall events are defined by depth and duration, which are found to be correlated. An analysis of the depth per event, given the event duration, has been undertaken. The negative binomial distribution appears to yield the best overall fit for the depth per event for one-day events. The duration of rainfall events follows a geometric distribution while that of dry events follows the negative binomial distribution. The chronological position of the first rainfall event in the rainy season seems to fit the loi de Fuites. These event based results are applied to generate synthetic sequences of rainfall and dry events and can be used for reservoir simulation studies, estimation of irrigation water demand and the studies of the effects of climate change.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)